2014
DOI: 10.1210/me.2014-1117
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Analysis of Histone Modifications in Human Endometrial Stromal Cells

Abstract: Dramatic changes of gene expressions occur in human endometrial stromal cells (ESCs) during decidualization. The changes in gene expression are associated with changes of chromatin structure, which are regulated by histone modifications. Here we investigated genome-wide changes in histone modifications associated with decidualization in human ESCs using chromatin immunoprecipitation combined with next-generation sequencing. ESCs were incubated with estradiol and medroxyprogesterone acetate for 14 days to induc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
100
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 57 publications
(107 citation statements)
references
References 53 publications
5
100
2
Order By: Relevance
“…We also found that the increase of H3K27ac in the distal regions as well as in the proximal regions was associated with the up-regulation of gene expression during decidualization (8). These facts led us to speculate that the H3K27ac-increased regions in the distal regions play key roles as enhancer regions in the regulation of gene expressions during decidualization.…”
mentioning
confidence: 52%
See 2 more Smart Citations
“…We also found that the increase of H3K27ac in the distal regions as well as in the proximal regions was associated with the up-regulation of gene expression during decidualization (8). These facts led us to speculate that the H3K27ac-increased regions in the distal regions play key roles as enhancer regions in the regulation of gene expressions during decidualization.…”
mentioning
confidence: 52%
“…Genome-wide analyses revealed a number of genes that are up-regulated or down-regulated by decidualization in human ESCs (5)(6)(7)(8). Gene expression including transcription involves a change of chromatin structure, which can be regulated by epigenetic mechanisms such as histone modifications (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Proper decidualization is essential for continued embryonic development within the uterus and achieving successful pregnancy, because impaired decidualization can lead to miscarriage or even pathological pregnancy such as preeclampsia or intrauterine growth restriction. 2,4 Genome-wide microarray analyses have identified a number of genes that are up-regulated or down-regulated during decidualization, suggesting the presence of complex mechanisms of gene expression. 4 To date, accumulating data have shown that gene expression involves a change of chromatin structure which can be regulated by structural proteins such as the high mobility group nucleosomal binding (Hmgn) family.…”
Section: Introductionmentioning
confidence: 99%
“…2,4 Genome-wide microarray analyses have identified a number of genes that are up-regulated or down-regulated during decidualization, suggesting the presence of complex mechanisms of gene expression. 4 To date, accumulating data have shown that gene expression involves a change of chromatin structure which can be regulated by structural proteins such as the high mobility group nucleosomal binding (Hmgn) family. 5,6 Hmgn proteins are architectural nonhistone chromosomal proteins that bind specifically to nucleosome core particle, reduce the compaction of the chromatin fiber, alter the structure of chromatin and thereby affect a variety of DNA-dependent activities such as transcription, replication, recombination and DNA repair.…”
Section: Introductionmentioning
confidence: 99%